Hepatic Fat and Inflammation in Type 2 Diabetes - Saremi, Aramesh (2009)
Although the association between inflammation and hepatic fat is fairly established, it remains unclear whether this association is independent of general measures of obesity and standard cardiovascular risk factors. Therefore, the aim of this study was to investigate the contribution of hepatic steatosis (HS) as an independent predictor of chronic inflammation in 281 subjects with type 2 diabetes. Hepatic steatosis significantly (p < 0.01) correlated with CRP (r= −0.16) and adiponectin (r=0.23). The association of HS with both CRP and adiponectin remained significant after adjustment for age, ethnicity, BMI (or WC), triglycerides, HDL, and total cholesterol. These data support the concept that accumulation of hepatic fat is related to enhanced inflammation in type 2 diabetes, independent of general measures of obesity and standard cardiovascular risk factors.